MAINTENANCE OF СА2+-ATP-ASE AMOUNT IN SARCOPLASMATIC RETICULUM CARDIOMYOCYTES IN ISCHEMIC MYOCARDIUM DURING SHORT DURATION OF DIABETES MELLITUS COURSE Kondratyeva D. S., Afansyev S. A., Kanev A. F., Kozlov B. N. - D. S. Kondratyeva; S. A. Afansyev; A. F. Kanev; B. N. Kozlov (Российский кардиологический журнал, 2014)
Aim. To study the level of Са2+-ATP-ase of sarcoplasmatic reticulum (SR) in human myocardium in ischemic heart disease (CHD) and in CHD with diabetes mellitus 2nd type (DM), and also in animals with postinfarction cardiosclerosis with DM.Material and methods. The study performed on biopsy material of the hearts from patients and rats with chronic ishemic heart disease wih DM. A piece of left atrial appendage (biopsy material) was cut away during the period of the artificial circulation device setup. Postinfarction cardiosclerosis (PICS) had being formed during 6 weeks after coronary artery occlusion. DM developed during 6 weeks after intraperitoneal injection of streptosotocine (60 mg/kg). The level of Са2+-ATP-ase was measured by immuneblotting.Results. It was shown that in both groups there were patients, whose myocardium contained high level of Са2+-ATP-ase and patients with low levels of this protein. At the same time myocardium of patients with CHD having high level of Са2+-ATP-ase, contained by 26,6%±0,53% (p<0,05) more of the protein studied, than myocardium of CHD patients with DM. Comparison of low Са2+-ATP-ase level patients did not show statistically significant difference between groups. Measurement of Са2+-ATPase in animals’ myocardium showed that ischemic and diabetic remodeling of myocardium leads to the decrease of Са2+-ATP-ase CP to 38,6±0,92% and 49±2,71%, resp. Concomitant development of these pathologies characterizes by the lowest amount of the protein studied and is 52,3±2,6% from controls.Conclusion. Myocardium of CHD patients, and rats with PICS shows higher level of Са2+-ATP-ase with DM with short disease duration.